STRUCTURAL DESIGN OF CONTAINER BERTH AT MAKASSAR NEW PORT PHASE 1B, MAKASSAR CITY, SOUTH OF SULAWESI - Tapian B. Nainggolan, Lawrensqy
Makassar City is one of the big cities on Sulawesi Island, precisely on the South Sulawesi region. Like other big cities, this city has rapid economic growth and must be facilitated by adequate infrastructure. The government projects Makassar New Port as a deep sea port which will become an economic gateway in the eastern region of Indonesia, especially on the South Sulawesi region. Beside of connecting Indonesia's regions, Makassar New Port was also built to become an international port that will connect Indonesia's logistic industries with other foreign countries. This final project will discuss the structural design of container berth with deck on pile type as a planning for the development of the Makassar New Port based on the design criteria used. The discussion in this final project includes environmental data processing, calculation of the load acting on the berth structure, determining the dimensions of berth and berth structural elements, structural analysis and modeling, reinforcement of berth structural elements, and soil bearing capacity analysis. The available environmental data and operational data will be processed to calculate the load acting on the berth. Structural analysis modelling was carried out using SAP2000 software to determine the strength of the berth structure against the working load. The results of berth structure modelling in the form of Unity Check Ratio (UCR) values and structural deflections must meet the design criteria, namely the UCR value is between 0.8 to 1.0 and the deflection value does not exceed the allowable deflection value. Reinforcement of the berth structural elements is carried out based on the internal forces obtained from the results of optimum structural analysis modeling. Soil bearing capacity analysis was also carried out to determine the required depth of piles needed to be able to withstand the load of the laying reaction on the berth structure. The results of the Berth design are the dimensions of the Berth as long as 308 m with a width of 43 m. The wharf is planned to have an elevation of +4.0 m from the LLWL, and a water depth of –14.5 from the LLWL. The structural elements planned for the berth include plates, beams, piles, and pile caps. The piles chosen after optimization are piles with a diameter of 1100 mm and a thickness of 20 mm which based on the analysis of the bearing capacity of the soil will be driven as far as 24.55 m from the elevation of seabed. The result of this final project is a structural design planning consisting of dimensions of berth, dimensions of berth structural elements, reinforcement of berth structural elements, and depth of berth piles.